Analisis Kecenderungan Dosen dan Mahasiswa Bahasa Indonesia di Semester 6 dalam Menggunakan Bahasa Baku dengan Bahasa Tidak Baku - Ayu Irani Oktavianti Seofeto; Sesiwarniwati Gulo; Heking Trisman Harefa; Noveri Amal Jaya Harefa (Departement of Mathematics Education, 2024)
The author's aim in conducting this research is to provide an understanding of the use of standard and non-standard language by Indonesian language lecturers and students, class B semester VI, within the scope of Nias University. The method used in this research is a qualitative method with a case study approach. The subjects of the research were Indonesian language lecturers and students, class B, sixth semester with the object being the use of standard and standard language at Nias University. Then the research instrument is used to assess the results through an assessment rubric. The assessment rubric starts from how to use standard and non-standard language, as well as how to pronounce it. After that, the technique used in data collection is observation, which involves direct observation by taking videos to be recorded as evidence. Then the Descriptive data analysis is used to provide an overview of standard and non-standard use. language by lecturers and students. As a result, the use of standard language is more dominantly used by lecturers than students, this is because the use of non-standard language is too inherent, which is triggered by increasingly advanced developments.